Our brain enjoys making friends - Gleichgerrcht, Ezequiel (2013)
Is it important to have friends? Why do we enjoy spending time with them? Do we learn differently around our friends? Neuroscience research is helping us to answer some of these questions by looking at the way our brain allows us to, and benefts from, interacting with other humans. Part of the reason why human brains are so complex is that our interactions with others are so complex; we are social creatures and have been living in groups for thousands of years. Our brain has developed the ability to handle the complexity of the social world that our species (human beings) have created. We organize our interactions into different levels of complexity: we tell apart our closest family members, we can help our neighbors, we belong to a nation, and we recognize ourselves as a part of the large world. But why have humans developed such complex social organizations? Interacting with others has been helpful to us as a species: there is something about cooperating with others that made us more ft to survive through evolution.